(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Most challenges that students confront can have an impact on academic success. This may take into account things like working while going to school. Many students make a point of working while in class. However, other students who are employed don’t truly struggle with money. Work part-time jobs that are linked to intended careers to develop abilities. The majority of students work due to difficulties with finances. The utilization of online learning demonstrates that it is quite beneficial during a pandemic to adapt to the new normal. Even though some students find it to be quite beneficial, some students are still struggling to adjust to the new learning environment. Many students are having difficulties as a result of the epidemic. Mostly those who work and study simultaneously. Others might lose jobs, which could have an impact on education. Due to a lack of funding, many families are unable to access education. Due to a lack of funding, many families are unable to access education. Requiring a student to continue working while a student to support the education Students’ GPAs higher than expected even if working a part-time job. However, compared to individuals who don’t have part-time employment, many working students took longer to complete degrees.